Patients with suspected cardiac amyloidosis. Role of endomyocardial biopsy. (14th October 2021) - Aguilera, C; Oteo Dominguez, J.F.O.D; Garcia Izquierdo Jaen, E.G.I.J; Dominguez Rodriguez, F.D.R; Garcia Touchard, A.G.T; Fernandez Diaz, J.A.F.D; Del Trigo Espinosa, M.T.E; Arellano Serrano, C.A.S; Sabater Altagracia, Y.S.A; Goicolea Ruigomez, F.J.G.R; Garcia Pavia, P.G.P; Salas Anton, C.S.A; et al.
Abstract: Introduction: Between the indications for endomyocardial biopsy (EMB) is the study of patients with heart failure associated with restrictive or infiltrative cardiomyopathy, such as cardiac amyloidosis if another workup is inconclusive. Although a risk-procedure, EMB is recommended in clinical scenarios in which the unique prognostic and diagnostic value of the information gained is felt to outweigh the procedural risks. Purpose: We want to know the diagnostic value of EMB in the scenario of suspected cardiac amyloidosis and the role of the place of EMB for diagnosis. Methods: We prospectively collected patients from our center with infiltrative cardiomyopathy and suspected cardiac amyloidosis who were referred to perform EMB. We gathered data on diagnostic profitability considering two different groups: those with samples from the right ventricle (group 1) and those with samples from the left ventricle (group 2; 90.8% with transradial approach). We consider major complications myocardial perforation, pericardial tamponade, arrhythmias, or bleeding with hemodynamic instability and death. Results: We collected data from 111 patients referred for EMB for infiltrative cardiomyopathy suspicion. We present the results in table 1. The most common diagnosis was cardiac amyloidosis for wild-type transthyretin (43.48% in group 1 and 58.46% in group 2). There were no complications in the patients with confirmed cardiac amyloidosis in group 2. Conclusions: In our EMBs for infiltrative cardiomyopathy suspicion we found that patients undergoing left-sided EMB had a shorter time of X-ray exposure and less time of admission without any other risk associated. So, we conclude that EMBs performed in the left heart are secure and comfortable for patients and physicians. Funding Acknowledgement: Type of funding sources: None.